The Impact of a Videogame-Based Pilot Physical Activity Program in Older Adults with Schizophrenia on Subjectively and Objectively Measured Physical Activity - Leutwyler, Heather; Hubbard, Erin; Cooper, Bruce; Dowling, Glenna (Frontiers in Psychiatry, 2015)
Objectives: The purpose of this report is to describe the impact of a videogame-based pilot physical activity program using the Kinect for Xbox 360 game system (Microsoft, Redmond, WA) on physical activity in older adults with schizophrenia. Methods: In this one group pretest posttest pilot study, twenty participants played an active videogame for 30 minutes, once a week for 6 weeks. Physical activity was measured by self-report with the Yale Physical Activity Survey and objectively with the Sensewear Pro armband at enrollment and at the end of the 6-week program. Results: There was a significant increase in frequency of self-reported vigorous physical activity. We did not detect a statistically significant difference in objectively measured physical activity although increase in number of steps and sedentary activity were in the desired direction. Conclusions: These results suggest participants’ perception of physical activity intensity differs from the intensity objectively captured with a valid and reliable physical activity monitor.